IMMIGRATION SUPERVISION OF FOREIGNERS APPLYING FOR RESIDENCE PERMITS IN INDONESIA - Duma Milanta; Mhd Azhali Siregar; Henry Aspan (International Journal of Synergy in Law, Criminal, and Justice, 2024)
To regulate the various types of foreign nationals leaving and entering Indonesian territory, government policy in the immigration sector adheres to the principle of selective policy, namely a policy based on selective principles. Based on this principle, only foreigners can provide benefits to the welfare of the people, nation and State of the Republic of Indonesia, who do not endanger security and order and are not hostile to either the people or the Unitary State of the Republic of Indonesia . In this research, researchers use normative legal studies, namely research that focuses on examining the application of rules or norms. The literature study was carried out with the aim of obtaining secondary data, namely through a series of reading, quoting and reviewing legislation related to the problem. The targets of supervision of foreigners in Indonesia are supervision of their whereabouts (immigration) and supervision of the activities of foreigners while they are in Indonesia. The aspect of monitoring the activities of foreigners requires coordinated activities between agencies in terms of implementing supervision. The Minister of Law and Human Rights as the coordinator at the Central (National) Level together with other relevant government bodies or agencies as the implementer of coordinated supervision of foreigners is called the Coordination of Supervision of Foreigners. A residence permit granted by a State to a foreigner is a form of State sovereignty as a legal State which has complete authority to determine and regulate restrictions for foreigners to stay in a State. This permission is not something that a foreigner can do, but is a privilege given by the State to foreigners